Menelaah Sumber Hukum yang Tidak Disepakati dalam Disiplin Ilmu Ushul Fiqh Beserta Implementasinya - M. Izzul Islam; Siti Tu’ta Khoirotul Khikmah; Lila Auliani An’nisa; Dhimas Ramadhani Arif Pratama; M. Imamul Muttaqin (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This observation aims to find out Islamic laws that aren’t agreed upon by the Ulama, including: Istihsan, Istishab, Mashlahah Mursalah, ‘Urf, Saddu Dzara’i, Madzhab Shahabat, and Syar’u Man Qablana and their implementation in daily life. The method used in this paper is library and journal research by collecting data using descriptive qualitative analysis. The results of the observations explain that in its development, the sources of Islamic law which became the basis for determining Muslim rules were divided into two, (1) The sources of Islamic law agreed upon by the Ulama (al-Quran, Hadits, Ijma’, and Qiyas); (2) The sources of Islamic law that aren’t agreed upon by Ulama (Istihsan, Istishab, Mashlahah Mursalah, ‘Urf, Saddu Dzara’i, Madzhab Shahabat, and Syar’u Man Qablana).